The role of spatially-derived access-to-care characteristics in melanoma prevention and control in Los Angeles county. (May 2017) - Escobedo, Loraine A.; Crew, Ashley; Eginli, Ariana; Peng, David; Cousineau, Michael R.; Cockburn, Myles
Abstract: Among 10, 068 incident cases of invasive melanoma, we examined the effects of patient characteristics and access-to-care on the risk of advanced melanoma. Access-to-care was defined in terms of census tract-level sociodemographics, health insurance, cost of dermatological services and appointment wait-times, clinic density and travel distance. Public health insurance and education level were the strongest predictors of advanced melanomas but were modified by race/ethnicity and poverty: Hispanic whites and high-poverty neighborhoods were worse off than non-Hispanic whites and low-poverty neighborhoods. Targeting high-risk, underserved Hispanics and high-poverty neighborhoods (easily identified from existing data) for early melanoma detection may be a cost-efficient strategy to reduce melanoma mortality.